Confidential review of maternal deaths in Kerala: a country case study - VP Paily; Ambujam; V Rajasekharan Nair; B Thomas (BJOG, 2014)
The Confidential Review of Maternal Deaths (CRMD) in Kerala was started in 2004, with support from the World Health Organization and modelled on the United Kingdom Confidential Enquiries into Maternal Deaths. It is carried out by the Kerala Federation of Obstetrics and Gynaecology with support from the government of Kerala. The leading causes of maternal deaths identified during the period 2004–09 were haemorrhage, hypertension, amniotic fluid embolism, heart disease and sepsis. Follow-up actions in the form of advocating for emergency preparedness, proper transport and standard protocols for management were initiated. Recently the international arm of the United Kingdom National Institute for Health and Clinical Excellence has helped to establish standards to improve obstetric care in Kerala based on the findings of the CRMD Kerala.